UJI LAPANG MESIN PENGOLAHAN SAGU PRODUKSI BENGKEL PERMESINAN AGROINDUSTRI UNIVERSITAS PAPUA - Darma Darma; Reniana Reniana; Arbianto Arif Moh. (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
Papua and West Papua Province have the large potential of sago palm (Metroxylon sagu), however, until now the production and utilization is very low compared with its potential. This is because of most farmers in this area still use traditional method in processing sago.  The traditional method is labour intensive and time consuming process.  Sago farmers in this area still apply traditional ways to process sago starch due to the lack of processing machines. The objective of this research was to conduct field testing of sago processing  machine produced by Agroindustry Machinery Workshop of Papua University. The machines that have been tested consist of cylinder type sago rasping machine and stirrer rotary blade sago starch extraction machine. The machine’s performance under field condition was evaluated by measuring parameters (a) rasping capacity, (b) extraction capacity, (c) starch percentage, (d) starch yield and (e) starch loss in waste. Results showed that all parts of the machine are functioning properly and farmers can easily operate the machine.  The performances of the machines under field condition were (a) rasping capacity 1,159. 8 kg/hour, (b) extraction capacity 243.8 kg/hour, (c) starch percentage 38.26 %, (d) starch yield 93 kg/hour   and (e) starch loss in waste 1.03 %.   Keywords: cylinder type, field test, rasping machine, sago processing, starch percentage